"Does Inflation Targeting Framework Make a Significant Difference in Lowering Price Level?” What is Its Implication to Indonesia’s Inflation Rate? - Faisal Rachman (Economics and Finance in Indonesia, 2015)
AbstractIn the last two decades many countries have been starting to employ Inflation Targeting Framework (ITF) as their main monetary policy framework. This is done to achieve an objective of anchoring public expectation on inflation which in the end will steer the price level movement towards ITF’s ultimate target of relatively low and stable inflation rate. By conducting Difference-in-Difference method on panel data consisting of five countries implementing ITF since 2001 and twenty-one selected non-ITF countries for period 1990-2010, it is statistically proved that ITF adoption has a significant effect on inflation. In case of Indonesia, through Structural Break approach, the implementation of ITF since 2005 is also proved able to lower and stabilize inflation rate.Abstrak Dalam dua dekade terakhir ini banyak negara yang telah mulai menggunakan Inflation Targeting Framework (ITF) sebagai kerangka utama kebijakan moneter mereka. Hal ini dilakukan guna mencapai tujuan pengendalian ekspektasi publik yang pada akhirnya akan mengendalikan pergerakan tingkat harga relatif rendah and stabil. Dengan menggunakan metode Difference-in-Difference pada data panel, yang terdiri dari lima negara yang telah mengimplementasikan ITF sejak tahun 2001 dan dua puluh satu negara bukan pengguna ITF, untuk periode 1990-2010, disimpulkan bahwa ITF memiliki dampak signifikan pada tingkat inflasi. Untuk kasus Indonesia yang telah mengimplementasikan ITF sejak tahun 2005, melalui metode Structural Break disimpulkan hasil yang sama, yaitu tingkatan harga yang rendah dan stabil.